STATEMENT OF MECHANICAL PROPERTIES OF MATERIALS WHICH HAVE ANALYZED - Edi Istiyono (Jurnal Penelitian Saintek, 2006)
The experiment  purposes  to observe  0(' (1)  the influence  of temperatureto the  [ensile strength   of  material.   (2) the  influence  of anneal  lime  to the tensile  strength  of material.   (3) the influence  (if temperature   to the torsion  modulus  (if material,   (4)  the  irfluence   (if anneal  lime  to  the torsion  modulus   of  material.   and  (5j  discover   the  material   that  has optimum  of tensile strength  and torsion  modulus.Sample  of the  experiment   is win! of  ion.  steel  and  copper  which  areannealed   011   temperature    of   15()°C,  25{)°C,  350°C,   45()"C,  550"C,650"C.  750°C. 850°C, and  950°Cfor   30 minutes.  Besides.  the wires are annealed  on temperature   350°Cfor    30.60,   9().120.  150. IBO. ]J()   and240  minutes.   The  tensile   strength   of  materials   is  measured   with  atensometer.   Tension  modulus   of  materials   is  measured   with  tension modulus  meter.Based   on  data   analysis    is  concluded    thai.   ( l )   Increasing    of  thetemperature   anneal  causes   decreasing   of  ttle  tensile  strength   of  the materials.   (2) increasing   of the  time  anneal  causes  decreasing   of the tensile  strength   (if  the  materials.    (3)  increasing   (if the  temperature anneal  causes  decreasing   of the torsion  modulus  of the materials.   (-/) increasing  of the anneal  time causes  decreasing  of the torsion  modulus of the materials.  and  (5) the optimum  tensile  strength  is the steel  which anneal   temperature    of  450°C  and  anneal   time   (if  30  minutes.   The optimum  torsion  modulus  is iron, which is not annealed.